Testing e-mail content to encourage physicians to access an audit and feedback tool: a factorial randomized experiment. - Vaisson, G.; Witteman, H. O.; Chipenda-Dansokho, S.; Saragosa, M.; Bouck, Z.; Bravo, C. A.; Desveaux, L.; Llovet, D.; Presseau, J.; Taljaard, M.; Umar, S.; Grimshaw, J. M.; et al. (Current Oncology, 2019)
Background In Ontario, an online audit and feedback tool that provides primary care physicians with detailed information about patients who are overdue for cancer screening is underused. In the present study, we aimed to examine the effect of messages operationalizing 3 behaviour change techniques on access to the audit and feedback tool and on cancer screening rates. Methods During May-September 2017, a pragmatic 2×2×2 factorial experiment tested 3 behaviour change techniques: anticipated regret, material incentive, and problem-solving. Outcomes were assessed using routinely collected administrative data. A qualitative process evaluation explored how and why the e-mail messages did or did not support Screening Activity Report access. Results Of 5449 primary care physicians randomly allocated to 1 of 8 e-mail messages, fewer than half opened the messages and fewer than 1 in 10 clicked through the messages. Messages with problem-solving content were associated with a 12.9% relative reduction in access to the tool (risk ratio: 0.871; 95% confidence interval: 0.791 to 0.958; p = 0.005), but a 0.3% increase in cervical cancer screening (rate ratio: 1.003; 95% confidence interval: 1.001 to 1.006; p = 0.003). If true, that association would represent 7568 more patients being screened. No other significant effects were observed. Conclusions For audit and feedback to work, recipients must engage with the data; for e-mail messages to prompt activity, recipients must open and review the message content. This large factorial experiment demonstrated that small changes in the content of such e-mail messages might influence clinical behaviour. Future research should focus on strategies to make cancer screening more user-centred.